Mission Drift in Microcredit and Microfinance Institution Incentives - Sara Biancini; David Ettinger; Baptiste Venet (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyze the relationship between Microfinance Institutions (MFIs) and external donors, with the aim of contributing to the debate on “mission drift” in microfinance. We assume that both the donor and the MFI are pro-poor, possibly at different extents. Borrowers can be (very) poor or wealthier (but still unbanked). Incentives have to be provided to the MFI to exert costly effort to identify the more valuable projects and to choose the right share of poorer borrowers (the optimal level of poor outreach). We first concentrate on hidden action. We show that asymmetric information can distort the share of very poor borrowers reached by loans, thus increasing mission drift. We then concentrate on hidden types, assuming that MFIs are characterized by unobservable heterogeneity on the cost of effort. In this case, asymmetric information does not necessarily increase the mission drift. The incentive compatible contracts push efficient MFIs to serve a higher share of poorer borrowers, while less efficient ones decrease their poor outreach.
Keywords: O12; O16; G21; 330; microfinance; donors; poverty; screening